A formal approach to reanalysis and the Early Semantic Stability Hypothesis: exploring the test case of the negative counterfactual marker ʾilmale in Hebrew and Aramaic - Bar-Asher Siegal Elitzur A. (Linguistics)
This study delves into the intricate process of reanalysis, wherein linguistic expressions undergo grammatical or semantic changes, or sometimes both. The primary objective of this study is to explore the theoretical aspects surrounding historical changes of this nature. To facilitate a comprehensive understanding of the topic, we provide a formal description of reanalysis as an analytical tool. Our formal description allows for the differentiation of various change scenarios, enabling us to identify distinct types of shifts from one analysis to another. This approach not only focuses on what has been reanalyzed, be it the morphology, syntax, or the semantics, but also emphasizes the interplay between all three linguistic modules (Form, Grammar, and Meaning) and their relationships. This holistic perspective enables a systematic examination of the significance of what remains constant at both points in time during the reanalysis process. The key insight arising from this analysis leads us to propose and substantiate the Early Semantic Stability Hypothesis. This hypothesis posits that the truth-conditional semantics of the original proposition remain unchanged throughout reanalysis, either in all contexts or in specific “bridging contexts” where the reanalysis occurs. To demonstrate these phenomena, we present a compelling test case, focusing on the development of the counterfactual conditional marker ʾilmale in Hebrew and Aramaic. Through a detailed examination of the syntactic and semantic reanalyses it underwent, we observe the emergence of unique semantic features. By adopting a formal semantic perspective, we address fundamental questions such as the level of ambiguity required for reanalysis to take place, the potential existence of universal constraints on reanalysis, and potential motivations driving these linguistic changes. This investigation provides valuable insights into the intricate mechanisms at play during reanalysis and contributes to the broader understanding of linguistic evolution and development.